2021
DOI: 10.1155/2021/8833527
|View full text |Cite
|
Sign up to set email alerts
|

NAT10 Promotes Osteogenic Differentiation of Mesenchymal Stem Cells by Mediating N4-Acetylcytidine Modification of Gremlin 1

Abstract: Objective. To investigate the function of NAT10 in mesenchymal stem cell (MSC) osteogenic differentiation and study the mechanism by which NAT10 affects MSC osteogenesis by mediating Gremlin 1 N4-acetylcytidine (ac4C) modification. Methods. Osteogenic differentiation of MSCs was induced, and the osteogenic ability was evaluated with alizarin red S (ARS) and alkaline phosphatase (ALP) assays. The NAT10 expression level during MSC osteogenesis was measured by western blot (WB). MSCs were transfected with lentivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…[1][2][3] Studies related to NAT10 mediated ac4C modification have shown its biological impact in many cellular events such as ribosome biogenesis, translational efficiency, bone remodelling, cell proliferation and epithelial to mesenchymal transition (EMT). 1,[4][5][6][7][8][9][10] N4-cytidine acetylation at position 1 773 (ac4C1773) of 18S rRNA is shown to be essential for 18S rRNA related RNA processing and ribosome biogenesis in saccharomyces cerevisiae. 4 Another study in human reported acetylation at position 1 842 (ac4C1842) evidently showing the impact of ac4C modification in 18S rRNA biogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] Studies related to NAT10 mediated ac4C modification have shown its biological impact in many cellular events such as ribosome biogenesis, translational efficiency, bone remodelling, cell proliferation and epithelial to mesenchymal transition (EMT). 1,[4][5][6][7][8][9][10] N4-cytidine acetylation at position 1 773 (ac4C1773) of 18S rRNA is shown to be essential for 18S rRNA related RNA processing and ribosome biogenesis in saccharomyces cerevisiae. 4 Another study in human reported acetylation at position 1 842 (ac4C1842) evidently showing the impact of ac4C modification in 18S rRNA biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Gremlin 1 is an antigonist of bone morphogenic protein 2 (BMP2) and BMP4 which play essential role in the bone development. 8 NAT10 promotes cell proliferation by acetylation CEP170 mRNA transcript in multiple myeloma. The stability of acetylated CEP170 transcript is associated with cell proliferation and chromosomal instability (CIN).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous viral vectors are widely used to modify the gene expression profile of MSCs, including retroviruses [ 9 , 10 ], lentiviruses [ 11 , 12 ], adenoviruses, adeno-associated viruses (AAVs) [ 13 , 14 ], baculoviruses [ 15 , 16 ]. Gene delivery using viral vectors exploits the natural capacity of viruses to infect MSCs and insert viral genes into the host genome, including any genes of interest (transgenes) ligated to the viral genome or replacing viral gene(s) ( Fig.…”
Section: Tools For Gene Deliverymentioning
confidence: 99%